The Relationship Between Academic Buoyancy And Academic Resilience In First-Year Students At The Faculty Of Health Universitas Padjadjaran - Dhiya Ulhaq Iriana; Iyus Yosep; Etika Emaliyawati (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2024)
Introduction: Academic resilience defined as the ability to survive and increase success in terms of education despite facing severe problems. Academic resilience in students can be formed if students are able to break down these problems into smaller problems and then deal with them properly. To be able to overcome these small or minor problems, students need good academic buoyancy. This study aims to analyze the relationship between academic buoyancy and academic resilience in first-year students at the faculty of health Universitas Padjadjaran.Method: The research design is a quantitative correlation with a cross-sectional time approach. The instruments used were the Indonesian version of the Academic Buoyancy Scale and the Academic Resilience Scale-30. The research population was 1082 first-year students of the 2022 class of the Faculty of Health. The sampling technique used was proportional stratified random sampling (n=162).Results: The results of the correlation analysis show that there is a strong and positive relationship between academic buoyancy and academic resilience (p = 0.000 and r = 0.679).Conclusions: There is a strong and positive relationship between academic buoyancy and academic resilience. Students should strive to maintain and improve their academic buoyancy and academic resilience, for example by building social connections, maintaining health, developing positive thoughts, and seeking help when needed.